Managing a crisis a practical guide - Curtin Tom; Hayman Daniel; Husein Naomi (Hampshire Palgrave, 2005)
This new practical guide explains what makes a crisis and who are the key players. It shows the importance of prior preparation and testing so that the company fully understands the crisis management environment and the importance of communications. Also
Keywords: Crisis management